2002
DOI: 10.1016/s0735-1097(02)01767-9
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopic characterization of human advanced atherosclerotic plaques

Abstract: The good ex vivo discrimination of histologically vulnerable and stable plaques in this study suggests that NIR spectroscopy has the potential to identify vulnerable atherosclerotic plaques in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 17 publications
2
100
0
Order By: Relevance
“…Similarly promising results of NIR spectroscopy to identify lipid-rich plaques have also been reported in human carotid endarterectomy and coronary autopsy specimens. 48,49 Although these ex vivo studies were performed in a blood-free laboratory setup, an in vivo rabbit aortic study showed the feasibility of intravascular NIR spectroscopy through blood by identifying lipid areas Ͼ0.75 mm 2 with 78% sensitivity and 75% specificity. 50 Although Raman spectroscopy has a theoretical advantage in direct quantification of individual plaque components, only a small percentage of photons are recruited into the Raman shift, which results in low signal-to-noise ratio and poor tissue penetration.…”
Section: Spectroscopymentioning
confidence: 99%
“…Similarly promising results of NIR spectroscopy to identify lipid-rich plaques have also been reported in human carotid endarterectomy and coronary autopsy specimens. 48,49 Although these ex vivo studies were performed in a blood-free laboratory setup, an in vivo rabbit aortic study showed the feasibility of intravascular NIR spectroscopy through blood by identifying lipid areas Ͼ0.75 mm 2 with 78% sensitivity and 75% specificity. 50 Although Raman spectroscopy has a theoretical advantage in direct quantification of individual plaque components, only a small percentage of photons are recruited into the Raman shift, which results in low signal-to-noise ratio and poor tissue penetration.…”
Section: Spectroscopymentioning
confidence: 99%
“…Based on this method, NIRS imaging within coronary artery allows for the chemical characterization of biological tissues and can be used to assess lipid and protein content in atherosclerotic plaques. In an experimental animal study and ex vivo validation studies, this modality was shown to accurately detect the lipid content within atherosclerotic plaques (63)(64)(65). The sensitivity and specificity to detect lipid component was 90% and 93%, respectively.…”
Section: Near-infrared Spectroscopy (Nirs)mentioning
confidence: 97%
“…There are three main areas of research regarding diffuse reflectance spectroscopy in the NIR and SWIR spectral ranges: 1) integrating sphere based measurements for estimating ex vivo tissue absorption and scattering coefficients; 2) fiber probe based "point" measurements to acquire reflectance measurements collected over small localized tissue volumes both in vivo and ex vivo; 3) imaging measurements both in vivo [1][2] and ex vivo that offer non-contact measurements of a larger area of tissues [3]. Previous studies based on fiber probe reflectance spectroscopy method have shown NIR and SWIR spectroscopy applications for distinguishing between ex vivo vulnerable and stable atherosclerotic plaques by estimating lipid-to-protein ratios [4][5], as well as distinguishing between ex vivo normal and cancerous breast tissue by estimating water and lipid volume fractions [6].…”
Section: Near-infrared Reflectance Spectroscopymentioning
confidence: 99%